Effecs of damage by wheat bug, Aelia germari [Hemiptera : Pentatomidae], on grain quality and on reproductive performance of the rice weevil, Sitophilus oryzae [Coleoptera : curculionidae] - Fourar, R.; Fleurat-Lessard, F. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
The wheat bug, Aelia germari, feeds on developing wheat kernels, causing a loss in baking quality of the harvested wheat (Triticum aestivum). The possible nutritional changes in the bug-damaged kernels after the harvest were tested in a bioassay using the rice weevil Sitophilus oryzae, which feeds on the kernel endosperm. The weevils were reared on baking wheat cultivar 'Manon demias', grown in Algeria, with different levels (0, 4, 8 and 13%) of wheat bug (A. germari) damaged kernels. Rice weevil reared on 4, 8 or 13% damaged wheat had a shorter development time than on wheat with no damage. However, pair-wise correlations showed that Dobie's index for susceptibility of grain for stored-products insect attack, number of progeny per female and kernel weight loss were not correlated with the percentage of damaged kernels. Using multivariate analysis, the general characteristics of high quality grain were associated with long development times for S. oryzae, low number of progeny, high baking strength, high falling number, high nitrogen, low ash content, and low assimilable nitrogen.